Clinical teaching practice and effect research of newly recruited nurses in the Department of Stomatology (口腔科新入职护士临床教学实践及效果研究) - LIANG Yu (梁宇); LI Jiahui (李嘉慧); CAI Shuang (蔡爽); SUO Shuai (索帅); ZHI Shengrui (只升睿); LIU Xuewei (刘学伟) (中西医结合护理)
Objective To explore the effect of stratified teaching method in teaching newly recruited dental nurses. Methods Newly recruited nurses in Stomatology Department of hospital in the past three years were selected as the teaching objects, the stratified teaching practice was carried out for the newly recruited nurses through various methods such as improving the teaching management system, establishing the teaching faculty, formulating the teaching training plan and comprehensive teaching evaluation. Results Through stratified teaching, the teaching results showed that the daily performance and examination results of nurses in the undergraduate group, the junior college group and the technical secondary school group after practice were better than those before practice, with a statistically significant difference (P＜0. 05). The performance of nurses in the undergraduate group was better than that in the junior college group and the technical secondary school group, with a statistically significant difference (P＜0. 05). Conclusion In accordance with student aptitude, stratified teaching method has achieved good teaching effect and is worth popularizing in clinical teaching of stomatology. (目的 探讨口腔科新入职护士分层临床教学方法和效果。方法 以医院近3年口腔科新入职护士为教学对象, 通过完善教学管理制度, 组建教学师资队伍, 制定教学培训计划及综合教学评价等各种方法, 来对新入职护士进行分层临床教学实践。结果 通过分层教学, 教学结果表明本科组、大专组、中专组三组新护士临床护理工作考核及年终考试培训后的成绩均优于培训前, 差异有统计学意义(P＜0. 05), 本科组的临床护理工作考核成绩优于大专组及中专组, 差异有统计学意义(P＜0. 05)。结论 分层教学能够根据三个层次护士不同情况因材施教, 教学效果良好, 值得在口腔临床教学中推广。)